Sensor material characterisation for magnetometer application - Zinal, Nabiah (2004)
AC and DC magnetic field measurements require a highly sensitive and stable magnetic sensor. In order to achieve these requirements, good properties and criteria of magnetic materials are identified. A few types of different magnetic materials have been used to study their characteristics and effect towards magnetic fields. The ring cores made from several different types of magnetic materials are designed having the same dimension so that they can be compared among each magnetic material easily. For this project, single and dual rod cores have been used as a fluxgate sensor core to observe the resulting sensor performance. Both sensors are tested with two magnetic sources; permanent magnet bar and solenoids with different diameters of wires. The output of each fluxgate sensor was processed to identify their relation with the test magnetic field density.